UPAYA MERANCANG PAUD DI MASA DEPAN UNTUK MENGATASI PROBLEMATIKA YANG KOMPLEKS - Maulidya Ulfah (AWLADY : Jurnal Pendidikan Anak, 2016)
AbstrakSome critical issues and problem in pre childhood education program recently, it actually has big influence to the growth of pre childhood education program in the future. Because of that, it is crucial by responding those critical issues in pre childhood education program. The main focus on those issues is: (a) Dichotomy PAUD and TPQ, (b) The incompetence Kindergarten teachers, (c) imbalance of right and duty’ kindergarten teachers, (d) the issues of 12 year obligatory education started from TK/RA. Based on that fact, it is needed some efforts in planning pre childhood education program in the future.